Patient Satisfaction Improvement by Comprehensive Holistic Services at Public Health Centre X Surabaya - Wartiningsih, Minarni; Silitonga, Hanna Tabita Hasianna; Ritunga, Imelda; Prayogo, Michelle Christina; Wijaya, Evelyn Danielle (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Comprehensive holistic health services are a form of improving the quality of health services by measuring IKM. The result of a survey by BPJS Kesehatan is that the IKM has not reached targeted satisfaction in 2016 and 2017. Public Health Center X has an index value that exceeds the existing IKM target, but the index value is lower than the index value in 2016. This study will analyze the decrease in the satisfaction index of BPJS participants towards First-Level Healthcare Facilities (FKTP). Then the low satisfaction index of BPJS participants getting their treatments in Public Health Center X. The study aims to understand the relationship between comprehensive holistic service and the satisfaction of outpatients at Public Health Center X. The research was an analytical observational study with a cross-sectional design. The samples obtained in this study were 242 respondents. The data were next processed using the PLS-SEM application. The results show that comprehensive holistic services affect satisfaction (t=7.983). The holistic service affects loyalty (t=6.112). The customer value affects satisfaction (t=2.155) and loyalty (t=3.527). Satisfaction affects loyalty (t=4.488). This research concludes that comprehensive holistic service and customer value affect satisfaction and loyalty. In addition, satisfaction has a direct effect on loyalty.